Interaction design of the Malaysian e-government portal. - Mahmud, Murni (IIUM Press, 2011)
The implementation of e-Government intends to provide better services to the malaysian citizens, as e-Government could reach a wider range of Malaysian population anytime and anywhere through its portal. The effectiveness of the e-Government portal could be measured from its interaction design. In this study, the protal interaction was evaluated using a heuristic evaluation method which comprised usability, accesibilty and attractiveness. The findings showed that the participants were satisfied with the portal's interaction design. However, the overall task performance was less efficient. The findings from this study has provided a better understanding of the interaction behaviour toward the Malaysian e-government portal and yielded some recommendations for better design of interaction.